A Compendium for Mycoplasma pneumoniae - Parrott, Gretchen L.; Kinjo, Takeshi; Fujita, Jiro (Frontiers in Microbiology, 2016)
Historically, atypical pneumonia was a term used to describe an unusual presentation of pneumonia. Currently, it is used to describe the multitude of symptoms juxtaposing the classic symptoms found in cases of pneumococcal pneumonia. Specifically, atypical pneumonia is a syndrome resulting from a relatively common group of pathogens including Chlamydophila sp., and Mycoplasma pneumoniae. The incidence of M. pneumoniae pneumonia in adults is less than the burden experienced by children. Transmission rates among families indicate children may act as a reservoir and maintain contagiousness over a long period of time ranging from months to years. In adults, M. pneumoniae typically produces a mild, "walking" pneumonia and is considered to be one of the causes of persistent cough in patients. M. pneumoniae has also been shown to trigger the exacerbation of other lung diseases. It has been repeatedly detected in patients with bronchitis, asthma, chronic obstructive pulmonary disorder and cystic fibrosis. Recent advances in technology allow for the rapid diagnosis of M. pneumoniae through the use of polymerase chain reaction (PCR) or rapid antigen tests. With this, more effort has been afforded to identify the causative etiologic agent in all cases of pneumonia. However, previous practices, including the overprescribing of macrolide treatment in China and Japan, have created increased incidence of macrolide-resistant M. pneumoniae. Reports from these countries indicate that >85% of M. pneumoniae pneumonia pediatric cases are macrolide-resistant. Despite its extensively studied past, the smallest bacterial species still inspires some of the largest questions. The developments in microbiology, diagnostic features and techniques, epidemiology, treatment and vaccines, and upper respiratory conditions associated with M. pneumoniae in adult populations are included within this review.